Le transfert maléfique : un nouveau motif du genre de l’horreur - Ischi, Stéphane; Gabay, Simon (Romanica Silesiana)
The present article discusses a motif of horror fiction, the “Evil transfer”, that remained unnoticed until now. The key idea of this motif is that, because evil is eternal and indestructible, it cannot be annihilated but only transferred. Four books and movies of the second half of the 20th c. have retained our attention: Thinner by Stephen King, The Exorcist by William Peter Blatty, It Follows by David R. Mitchell and the Ring trilogy by Kôji Suzuki. However, these rather recent examples must not hide the diachronic depth of such a motif: Renaissance humanists or biblical texts also present a similar idea. Key words: motif (narrative), curse, horror fiction, horror films